Acute Hepatitis of Unknown Origin (AHUO) in an Infectious Disease Referral Hospital: A Case Report - Maemun, Siti; Widiantari, Aninda Dinar; Setyawati, Ernie; Aliza, Nur; Setiawaty, Vivi; Rahmartani, Lhuri Dwianti (Bangladesh Journal of Medicine, 2025)
Background The World Health Organization (WHO) reported Acute Hepatitis of Unknown Aetiology (AHUA) occurred in children in several countries, including Indonesia. Before this study was conducted, the cause and treatment were unknown. The Ministry of Health reported 91 cases in less than 16 years old children which spread across 22 provinces in Indonesia. This is a case report which was part of a surveillance program at Sulianti Saroso Infectious Disease Hospital (SSIDH) in 2023. The treated probable AHUA case was 16 years and 10 months old, while other studies reported probable AHUA cases ≤16 years old. Case presentation Of the 17 patients suspected AHUA who were treated at SSIDH, one case was categorized as probable AHUA. The patient was a 16 years old 10 months-old Javanese boy, who was first admitted to the Primary Health Centre (PHC). Clinical symptoms were abdominal pain 7 days before hospital admission, nausea, vomiting, dizziness, diarrhoea, brownish-yellow urine, decreasing appetite, and jaundice for 3 days before hospital admission. No history of COVID-19 and he has received the COVID-19 vaccine twice. He was undernourished. Alanine aminotransferase (ALT), aspartate aminotransferase (AST) and bilirubin levels were elevated. Tests for hepatitis B (HBsAg), hepatitis C virus (HCV) antibodies (Ab), hepatitis A IgM, and hepatitis E IgM were all negative. Length of Stay (LoS) hospitalisation was 12 days, and the patient has recovered. Conclusions Adequate identification and management of cases were carried out by paediatricians so that severe conditions do not occur. Bangladesh J Medicine 2025; 36(2): 142-148